Constructing The Lyrical Persona: A Transitivity Analysis of Raye’s “Where Is My Husband!” - Friska Dita; Dyah Suryaningrum; Theodore Alexander Atmaja (BLESS, 2026)
As a form of discourse, song lyrics linguistically represent experiences, emotions, and identities. While previous studies have applied Systemic Functional Linguistics (SFL) to analyze transitivity in song lyrics, few have examined how transitivity contributes to constructing the lyrical persona's identity. This study examines how transitivity constructs the identity of the lyrical persona in Raye’s “Where Is My Husband!” using a qualitative descriptive approach. All clauses in the official lyrics were analyzed using Halliday and Matthiessen's transitivity framework and interpreted through Bucholtz and Hall's discourse-based theory of identity construction and the lyrical persona concept by Culler. The analysis identified 130 processes, with material processes occurring the most frequently, followed by mental, verbal, relational, and behavioral processes. However, the existential processes were absent in the findings. These suggest that the transitivity configurations construct the lyrical persona collectively as an individual characterized by active longing, emotional expectation, communicative persistence, and relational incompleteness. The study shows that transitivity analysis can explain how experiential meanings contribute to identity construction in contemporary song lyrics.